Ningpoensines A–C: unusual zwitterionic alkaloids from Scrophularia ningpoensis. Issue 40 (30th September 2015) - Zhang, Jun; Ip, Fanny C.F.; Tong, Estella P.S.; Chan, Kim Wan; Li, Liang-Chun; Ng, Yu Pong; Ip, Nancy Y.
Graphical abstract: Abstract: Three novel zwitterionic alkaloids—ningpoensine A (1 ) and a pair of epimers, ningpoensines B/C (2a /2b )—with unprecedented molecular skeletons were isolated from the root of Scrophularia ningpoensis . Their structures were established by extensive spectroscopic analyses, and the absolute configuration of ningpoensine A was determined by quantum chemical calculations. A biosynthetic pathway leading to ningpoensines A–C from harpagide and natural amino acids is proposed. Ningpoensines B/C tended to promote wound closure in human embryonic keratinocytes.